2000
DOI: 10.1590/s0100-84042000000100003
|View full text |Cite
|
Sign up to set email alerts
|

The developmental anatomy of the subterranean system in Mandevilla illustris (Vell.) Woodson and M. velutina (Mart. ex Stadelm.) Woodson (Apocynaceae)

Abstract: The developmental anatomy of the subterranean system in Mandevilla illustris (Vell.) Woodson (Apocynaceae)). Two species of Mandevilla from the savanna area of São Paulo State, Brazil were studied. These species have been prescribed as folk medicine as infusions or alcoholic extracts of the underground system for treatment of venomous snake bites. To explain the morphological nature of such a system, its ontogeny was described to determine which parts are involved in its formation. In both Mandevilla specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
13

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 15 publications
0
14
0
13
Order By: Relevance
“…Therefore, three types of underground organs could be identified in the same genus and tribe of the Asteraceae, showing their morphological diversity. The occurrence of xylopodia has been recorded in Brazilian Cerrado species belonging to different taxa (Appezzato-da-Glória and Estelita, 2000;Milanez and Moraes-Dallaqua, 2003), including Asteraceae representatives (Paviani, 1987(Paviani, , 1977. In some species, the lower portion of the xylopodium is joined to the upper portion of the tuberous root, as in Mandevilla illustris, M. velutina (Appezzato-da-Glória and Estelita, 2000), and Pachyrhizus ahipa (Milanez and MoraesDallaqua, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, three types of underground organs could be identified in the same genus and tribe of the Asteraceae, showing their morphological diversity. The occurrence of xylopodia has been recorded in Brazilian Cerrado species belonging to different taxa (Appezzato-da-Glória and Estelita, 2000;Milanez and Moraes-Dallaqua, 2003), including Asteraceae representatives (Paviani, 1987(Paviani, , 1977. In some species, the lower portion of the xylopodium is joined to the upper portion of the tuberous root, as in Mandevilla illustris, M. velutina (Appezzato-da-Glória and Estelita, 2000), and Pachyrhizus ahipa (Milanez and MoraesDallaqua, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Several representatives of this family and of others have thickened underground systems (FigueiredoRibeiro et al, 1986;Tertuliano and FigueiredoRibeiro, 1993) and due to the scarce information about their morphology and anatomy, the designation of these organs is confused (Rizzini and Heringer, 1961;Appezzato-da-Glória and Estelita 2000). The genus Vernonia (tribe Vernonieae) contains about 500 species distributed in North and South America, tropical Africa, Madagascar and tropical Asia (Bremer, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Despite of the fact that Auderset et al (1997) reported the advantageous effects of compounds with SH group-protecting agents such as DTT for enhancing the formation of roots in difficult-to-root woody cuttings, DTT treatments were not effective in rooting M. velutina microcuttings. Handro et al (1998) reported root formation of M. velutina plantlets in full strength MS medium supplemented with auxins but the percentage of rooted and acclimatized plants was not informed.…”
Section: Micropropagationmentioning
confidence: 93%
“…Woodson, a subshrub that belongs to the Apocynaceae family, is a perennial endemic plant from the Brazilian "Cerrado". Apezzato-da-Glória & Estelita (2000) investigated the nature of the subterranean systems of this species and revealed that it encloses xylopodium and a tuberous root system. The extract of M. velutina underground systems is widely used against snake bites and as an anti-inflammatory agent.…”
Section: Introductionmentioning
confidence: 99%
“…Ex Stadelm.) Woodson consists of a xylopodium, the basal region of which is joined to a tuberous root (Appezzato-da-Glória and Estelita, 2000). We collected M. velutina tuberous roots at a site (19°09'20" S, 48°23'20" W) in the Brazilian cerrado (savanna) near the town of Uberlândia in the Brazilian state of Minas Gerais.…”
Section: Crude Chemical Compounds and Mediamentioning
confidence: 99%